Optimizing Newborn Outcomes in Cesarean Sections: A Comparative Analysis of Stress Indicators under General and Spinal Anesthesia - Anna Uram-Benka; Izabella Fabri-Galambos; Marina Pandurov-Brlić; Goran Rakić; Nikola Bošković; Jasminka Uram-Dubovski; Jelena Antić; Dejan Dobrijević (MDPI AG, 2024)
Background and Objectives: The moment of birth represents a complex physiological process that is followed by adaptive changes in the vital systems of the newborn. Such reactions have their positive but also negative effects. The aim of this research was to determine the difference in laboratory values of stress indicators in newborn children delivered by cesarean section (CS) with general and spinal anesthesia. We attempted to make a recommendation about the optimal type of anesthesia based on our results. Materials and Methods: The study was performed on 150 healthy term newborns delivered by urgent or planned CS. Samples for adrenocorticotropic hormone (ACTH), cortisol, triglycerides, and interleukin-6 (IL-6) were analyzed. Results: Leukocyte numbers, triglycerides, and blood sugar values were normal for the newborns' age, with statistically significantly lower values of blood sugar and triglycerides in newborns delivered by CS in spinal anesthesia (p < 0.005) compared to general anesthesia. There were no significant differences in ACTH, cortisol, and IL-6 levels between those newborns delivered via CS after spinal or general anesthesia. Conclusions: In cases where vaginal delivery is not possible, when CS is indicated, the use of well-controlled spinal anesthesia is followed by lower degrees of metabolic, inflammatory, and stress responses and better vitality of the baby upon birth.